Wind Power Harnessing in Sudan, Opportunities and Challenges - M. A Khadam, Ashraf; Hamouda, El Amin; R. Doud, Kamal (University of Khartoum Engineering Journal, 2022)
The African continent is endowed with large renewable potential, varying in types across diverse geographic areas. Wind resources are of the highest quality in the north, the east, and the southern regions [1]. This study concentrates on Sudan as one of African countries; that possess a good potential in wind power which can be integrated to support national grid as well as future regional power grid. This study uses windPRO 3.0.651 package [2] which is a software of wind energy project design and planning. In this study a comprehensive analysis for wind power in Sudan was done to verify the wind power potential in Sudan.